SAX-HPLC and HSQC NMR Spectroscopy: Orthogonal Methods for Characterizing Heparin Batches Composition - Spelta, Franco; Liverani, Lino; Peluso, Alessandra; Marinozzi, Maria; Urso, Elena; Guerrini, Marco; Naggi, Annamaria (Frontiers in Medicine, 2019)
Heparin is a complex mixture of heterogeneous sulfated polysaccharidic chains. Its physico-chemical characterization is based on the contribution of several methods, but advantages of the use of complementary techniques have not been fully investigated yet. Strong-Anion-Exchange HPLC after enzymatic digestion and quantitative bidimensional 1H-13C NMR (HSQC) are the most used methods for the determination of heparin structure, providing the composition of its building blocks. The SAX-HPLC method is based on a complete enzymatic digestion of the sample with a mixture of heparinases I, II and III, followed by the separation of the resulting di- and oligo-saccharides by liquid chromatography. The NMR-HSQC analysis is performed on the intact sample and provides the percentage of mono- and di-saccharides by integration of diagnostic peaks. Since, for both methods, accuracy cannot be proved with the standard procedures, it is interesting to compare these techniques, highlighting their capabilities and drawbacks. In the present work, more than 30 batches of porcine mucosa heparin, from 8 manufacturers, have been analyzed with the two methods, and the corresponding results are discussed, based on similarities and differences of the outcomes. The critical comparison of both common and complementary information from the two methods can be used to identify which structural features are best evaluated by each method, and to verify from the concordance of the results the accuracy of the two methods, providing a powerful tool for the regular characterization of single, commercial preparations of Heparin.